PENGARUH KUALITAS AUDITOR, UKURAN PERUSAHAAN, LEVERAGE, DAN PROFITABILITAS TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR GO PUBLIK DI INDONESIA - Jansen Fernando Sandjaya Leko, 10.05.52.0144; Setyowati, Widhy (Students Journal of Accounting and Banking, 2015)
This study is the test and analyze the effect of auditorâs quality, firm size, leverage, and profitability on earnings management in manufacturing companies that went public in Indonesia. The population in this study are manufacturing companies listed in Indonesia Stock Exchange 2011-2013. The procedure used to determine the sample is purposive sampling method sampling technique with particular consideration. According to predetermined criteria contained 73 samples. The analysis technique used is multiple linear regression. Based on the test results it can be concluded that the auditorâs quality and company size has no effect on earnings management. Leverage, and profitability positive effect on earnings management.Keywords: Auditorâs Quality, Firm Size, Leverage, Profitability and Earnings Management